Tinjauan Ketepatan Kode Penyakit Gastroenteritis di Rumah Sakit (Literature Review) - Anisa Dewi Wahyuni; Noor Yulia; Nanda Aula Rumana; Laela Indawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Factors of completeness of medical record documents, medical personnel, coding infrastructure, coders, and policies affect the coding of gastroenteritis diagnoses where inaccuracy due to this can cause a decrease in service quality, inaccurate report data, and errors in billing for services that have been provided by the hospital. This study aims to identify the accuracy of coding gastroenteritis disease and the factors that cause inaccuracy in coding gastroenteritis disease based on the 5M elements. The research method uses the literature review method with the PICO framework, P = Medical records of gastroenteritis patients, I = Gastroenteritis, O = Accuracy of coding of gastroenteritis disease. The inclusion criteria in this study are journals that discuss the accuracy and accuracy as well as the factors of inaccuracy and inaccuracy of gastroenteritis disease codes. The results of the 10 journals analyzed showed that the lowest code accuracy was 0% in 2 journals, while the highest percentage reached 91.5% in 1 journal. The most common factor in the inaccuracy of gastroenteritis codes is found in the man factor, namely the diagnosis provided by doctors is often incomplete or not written at all, and coding is often not based on other supporting information. Coders also lack mastery in analyzing medical record documents and errors in disease coding are related to coder knowledge. In addition, communication between coders and doctors was not effective. Increased training and provision of adequate resources to improve the accuracy of disease coding are needed.